2009
DOI: 10.1002/ana.21581
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of central nervous system remyelination by induced differentiation of oligodendrocyte precursor cells

Abstract: Our studies demonstrate that LINGO-1 antagonism promotes OPC differentiation and remyelination, and suggest LINGO-1 functions as an inhibitor of OPC differentiation to retard central nervous system remyelination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
201
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 283 publications
(206 citation statements)
references
References 28 publications
3
201
0
2
Order By: Relevance
“…On the other hand, LINGO-1-deficient mice or mice treated with an anti-LINGO-1 antibody exhibited greater remyelination and functional recovery when submitted to EAE (Mi et al 2007). The same observations were made when animals were submitted to toxin-induced demyelination (Mi et al 2009). As for the Wnt signaling pathway, Fancy et al (2009) identified pathway-associated genes that are induced during remyelination in mice submitted to experimental demyelination.…”
Section: Underlying Mechanisms In Demyelination/ Remyelination Processessupporting
confidence: 53%
“…On the other hand, LINGO-1-deficient mice or mice treated with an anti-LINGO-1 antibody exhibited greater remyelination and functional recovery when submitted to EAE (Mi et al 2007). The same observations were made when animals were submitted to toxin-induced demyelination (Mi et al 2009). As for the Wnt signaling pathway, Fancy et al (2009) identified pathway-associated genes that are induced during remyelination in mice submitted to experimental demyelination.…”
Section: Underlying Mechanisms In Demyelination/ Remyelination Processessupporting
confidence: 53%
“…Mice deficient in LINGO-1 or treated with an antibody antagonist against LINGO-1 exhibited increased remyelination and functional recovery from EAE, a model of immune-mediated demyelination [53]. Moreover, the LINGO-1 antagonist is able to promote CNS remyelination by directly stimulating OPC differentiation in nonimmune, toxin-induced models of demyelination in rats [54]. These findings reveal the importance of LINGO-1 signaling in regulating OPC differentiation in the injured CNS.…”
Section: Pharmacological Targets Of Remyelinationmentioning
confidence: 79%
“…Attenuation of LiNGo-1 function in oPCs by siRNA, dominant-negative LiNGo-1, LiNGo-1-Fc or LiNGo knockout, invariably promotes oPC differentiation and myelination in vitro [48][49][50][51] . Blockade of LiNGo-1 signaling promotes myelination in oPC-DRG co-cultures and LPC-treated cerebellar slice cultures [50,52] .…”
Section: Lingo-1mentioning
confidence: 99%